Migration and Asset Accumulation in South India : Comparing Gains to Internal and International Migration from Kerala - Seshan, Ganesh (World Bank, Washington, DC, 2020)
This study examines the asset gains to households in Kerala, India, from two types of labor migration: moving overseas versus moving within India for employment. It draws on panel data from waves of a representative household survey conducted in 1998 and 2003. Migrant households as a whole experienced higher asset gains than non-migrant families over this five-year period. Contrary to theoretical expectations, asset gains were similar for households with an overseas migrant and those with a domestic migrant. Although less educated individuals tend to venture overseas, a wage premium over non-migrants enables them to earn as much in low-skill jobs abroad as more educated workers relocating within India can.